Mutations in the gamma(2) subunit of AMP-activated protein kinase cause familial hypertrophic cardiomyopathy: evidence for the central role of energy compromise in disease pathogenesis. - Blair, E; Redwood, C; Ashrafian, H; Oliveira, M; Broxholme, J; Kerr, B; Salmon, A; Ostman-Smith, I; Watkins, H (2001)
Familial hypertrophic cardiomyopathy (HCM) has been widely studied as a genetic model of cardiac hypertrophy and sudden cardiac death. HCM has been defined as a disease of the cardiac sarcomere, but mutations in the known contractile protein disease genes are not found in up to one-third of cases. Further, no consistent changes in contractile properties are shared by these mutant proteins, implying that an abnormality of force generation may not be the underlying mechanism of disease. Instead, all of the sarcomeric mutations appear to result in inefficient use of ATP, suggesting that an inability to maintain normal ATP levels may be the central abnormality. To test this hypothesis we have examined candidate genes involved in energy homeostasis in the heart. We now describe mutations in PRKAG2, encoding the gamma(2) subunit of AMP-activated protein kinase (AMPK), in two families with severe HCM and aberrant conduction from atria to ventricles in some affected individuals (pre-excitation or Wolff-Parkinson-White syndrome). The mutations, one missense and one in-frame single codon insertion, occur in highly conserved regions. Because AMPK provides a central sensing mechanism that protects cells from exhaustion of ATP supplies, we propose that these data substantiate energy compromise as a unifying pathogenic mechanism in all forms of HCM. This conclusion should radically redirect thinking about this disorder and also, by establishing energy depletion as a cause of myocardial dysfunction, should be relevant to the acquired forms of heart muscle disease that HCM models.